2017
DOI: 10.1007/bf03399433
|View full text |Cite
|
Sign up to set email alerts
|

Immigration and Swiss House Prices

Abstract: SUMMARYThis study examines the behavior of Swiss house prices in relation to immigration flows for 85 regions from 2001 to 2006. The results show that the nexus between immigration and house prices holds even in an environment of low house price inflation and modest immigration flows. An immigration inflow equal to 1 % of an area's population is coincident with an increase in prices for single-family homes of about 2.7 %, a result consistent with previous studies. The overall immigration effect for single-fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
25
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 28 publications
(37 reference statements)
8
25
0
3
Order By: Relevance
“…Previous research has found estimates of positive sign and similar magnitude. The coefficients for both house prices are very similar to existing IV estimated elasticities, such as Saiz (2007) (who finds 0.9 for rents and 3.2 for prices), Degen & Fischer (2010) who find 2.7 for Swiss prices, González & Ortega (2009) who find 3.2 for house prices and Ottaviano & Peri (2007) who find 0.7 for rents and between 1-2 for prices.…”
Section: Effect Of Immigration On House Pricessupporting
confidence: 82%
See 1 more Smart Citation
“…Previous research has found estimates of positive sign and similar magnitude. The coefficients for both house prices are very similar to existing IV estimated elasticities, such as Saiz (2007) (who finds 0.9 for rents and 3.2 for prices), Degen & Fischer (2010) who find 2.7 for Swiss prices, González & Ortega (2009) who find 3.2 for house prices and Ottaviano & Peri (2007) who find 0.7 for rents and between 1-2 for prices.…”
Section: Effect Of Immigration On House Pricessupporting
confidence: 82%
“…When I refer to house prices as opposed to rents, the term corresponds to transaction prices. 4 Other studies include Stillman & Maré (2008) who provide positive impact estimates for New Zealand; Degen & Fischer (2009) who find positive effects for Switzerland; Akbari & Aydede (2012) find positive but small impacts in Canada; Frostad (2014) estimates the impact in Norway; and Kürschner (2017) for Germany. More recently, Tumen (2016) study the impact of the Syrian refugees inflow on Turkish housing rents and finds a positive effect on high quality units and no effect on low-quality units.…”
Section: Introductionmentioning
confidence: 99%
“…They estimated an annual 2% increase in housing prices, and a 1.2-1.5% increase in housing units. Degan & Fisher [31] likewise found a 2.7% growth in housing prices correlating with a 1% growth in the immigrant population in Switzerland, despite a flat market and a low level of immigration. Sà [32], on the other hand, identified a negative correlation between immigration and housing prices due to the previously-mentioned mobility of the native population.…”
Section: Housing Prices and Immigrationmentioning
confidence: 85%
“…Gonzales and Ortega [26] measured the correlation between the housing market boom in Spain (2000-2010) and the rising of immigration. Furthermore, a 2.7% growth in housing prices in Switzerland is correlated with a 1% growth in the immigrant population, despite a flat market and a low level of immigration [27]. On the contrary, others identified in the UK a negative correlation between immigration and housing prices due to the mobility of the native population facing foreign resident's concentration [28].…”
Section: The Housing Market and The Living Conditions Of Immigrants Imentioning
confidence: 99%